Post-cutting Mortality Following Experimental Silvicultural Treatments in Unmanaged Boreal Forest Stands - Montoro Girona, Miguel; Morin, Hubert; Lussier, Jean-Martin; Ruel, Jean-Claude (Frontiers in Forests and Global Change, 2019)
Partial cutting has been recommended as an alternative harvesting method to ensure the sustainable management of boreal forests. The success of this approach is closely linked to the survival of residual trees as additional losses through mortality could affect post-cutting timber production at harvest. To better quantify post-cutting mortality in previously unmanaged boreal forests, we addressed two main questions: (1) what is the level of mortality ten years after cutting? and (2) what ecological factors are involved in this phenomenon? Even-aged black spruce [Picea mariana (Mill.) B.S.P.] stands in the Canadian boreal forest were subjected to three experimental shelterwood treatments, a seed-tree treatment and an untreated control. Tree status (live/dead) was recorded prior to cutting and ten years after cutting. Dead trees were classified as standing dead, overturned or broken. Ten years after experimental seed-tree treatment, 60% of residual trees were dead, compared to 30% for the shelterwood cuttings. Windthrow (overturned and broken trees) represented 80% of residual tree mortality; only the amount of overturning was influenced by treatment. Broken trees were associated with small-diameter trunks, stands having high growth prior to cutting, younger stands or forest plots located near to adjacent cuts (<200 m). Overturning was associated with a high harvesting intensity and large-diameter trees. Standing dead mortality was the most difficult to explain: it was related to untreated plots having suppressed and small-diameter trees. Based on these results, applying intermediate levels of harvest intensity could reduce post-cutting damage. Understanding tree mortality after cutting is essential to reduce economic losses, improve silvicultural planning and stand selection and ensure ultimately the sustainable harvest of North American boreal forests.